T helper cell priming of mice to Borrelia burgdorferi Osp A leads to induction of protective antibodies following experimental but not tickborne infection - Zhong, Weimin; Gern, Lise; Kramer, Michael; Wallich, Reinhard; Simon, Markus M (My University, 1997)
Antibodies to the outer surface lipoprotein A (Osp A) of Borrelia burgdorferi confer protection to SCID mice against subsequent tick-borne or experimental infection. However, Osp A-specific antibodies are hardly detectable in naturally infected humans, dogs, hamsters and mice. This is most probably due to limited expression of Osp A on spirochetes transmitted from the vector to the host. Here we have tested whether T cell priming of mice would lead to the induction of protective Osp A-specific antibodies upon infection. It is shown that AKR/N mice, previously immunized with either a single T helper cell peptide of Osp A, or a mixture of 27 peptides spanning the entire molecule, develop Osp A-specific IgM or IgG antibodies, including those to a prominent protective B cell epitope of Osp A, LA-2, within 7 days of infection with low doses (103) of culture-derived spirochetes. In marked contrast, the same groups of pre-sensitized mice failed to generate any detectable Osp A-specific antibodies after tick-borne infection for more than 40 days after infection. All mice, irrespective of their state of T cell immunity to OspA or the mode of infection, produced similar levels of Osp C-specific IgM and IgG antibodies as early as day 14 after infection. None of the mice previously immunized with Osp A peptides were protected against experimental infection, in spite of the appearance of protective antibodies. It is clear from these data that, in contrast to culture-derived spirochetes, the naturally transmitted pathogen fails to express Osp A within the mammalian host at levels sufficient for induction of B cell responses, even in the presence of pre-activated T helper cells. Together with the fact that Osp A-specific antibodies are mainly operative by eliminating spirochetes from the vector during infestation, the data suggest that Osp A-vaccination for T helper cell immunity alone is not sufficient to prevent Lyme disease.
Keywords: Lyme disease; Vaccination; T cell epitope; T helper cell; Outer surface protein A